Contaminant fate and transport in double-porosity soil medium using light transmission visualization technique - Alazaiza, Motasem Y D (2017)
Non-aqueous phase liquid is a common form of groundwater and soil contamination. Petroluem products, as an example of these liquids, have a high potential of leaking into groundwater due to industrial and transportation activites. Double-porosity is a natural phenomenon that can be found in many types of soil. Its presence in the subsurface system can significantly affect the behaviour of geomaterials as well as the multiphase fluid flow through it due to the presences of two types of porosities. This research was undertaken to study the behaviour of one type of the most wide spread contaminant which is the non-aqueous phase liquids (NAPLs) migration in double-porosity soil under different conditions using light transmission visualization (LTV) technique. The NAPLs considered in this study are the resulted from chlorinated solvents and petroleum compounds such as tetrachloroethlene (PCE) and toluene. The double-porosity media composed of a mixture of local silica sand (macro-pores) and sintered kaolin clay spheres (micro-pores) arranged in a periodic manner. The laboratory experiments were designed and carried out under different conditions which represent the NAPL migration in two-fluid phase systems, three-fluid phase systems and the NAPL migration under the influence of rainfall recharge. Five experiments were repeated using a single-porosity media to investigate the influence of the macro-pores between the sand and kaolin spheres on the NAPL migration. Macor-pores was found to be an influential in the NAPL migration since the volume of macro-pores is very large as compared to micro-pores. Prior of starting the laboratory expriments, equations were derived to calculate the Dense NAPL (DNAPL) saturation in double-porosity pixel by pixel based on LTV method. The usage of the LTV technique can instantaneously capture the DNAPL migration in the porous media. The captured images were fed through an image processing software, transforming the digital images into grey level values that were subsequently used in the re-creation and plotting of the DNAPL distribution process. The results demonstrated that the LTV technique and image analysis were successfully combined to obtain the DNAPL saturation in double-porosity. The method was validated using mass balance where the injected volumes of DNAPL were compared to the calculated volumes using image analysis. Moreover, statistical analysis was used to validate the accuracy of the method. Strong correlation was obtained between the injected DNAPL volumes and the calculated volumes in all of the experiments (R2 > 0.90). The results show a slight difference between the means of the repeated experiments which indicates that the method is viable for monitoring DNAPL migration in double-porosity medium. Furthermore, the results show that the macro-pores have a significant effect on both LNAPL and DNAPL migration in double-porosity soil where the NAPL was much faster in double-porosity soil compared to single-porosity soil due to the volume of the macro-pores. Wettability of fluids and capillary pressure characteristics that exist in the soil pores were found to be influential factors in fluid migration within porous media. The occurrence of the wettability in the three-fluid phase system caused the NAPL to be more slower as compared to the migration in two-fluid phase system. In addition, the results show that chemical properties such as retardation factor and distribution coefficient have a significant influence on the LNAPL and DNAPL migration in porous media. Rainfall recharge was found to be an influential factor on the light non-aqueous phase lqiuid (LNAPL) migration in double-porosity soil. The flow of rainwater that seeped thrpugh the soil caused the LNAPL entrapped in the porous media to be pushed downward in all the experiments regardless of the LNAPL volume and rainfall intensity. Furthermore, it vi was observed that the capillary fringe level was depressed in the saturated zone due to the influence of the rainfall on LNAPL plume. Overall, the application of the LTV technique successfully provides a non-intrusive and non-destructive tool in investigating the NAPL behaviour in double-porosity soil media in multiphase fluid flow without disturbing the soil samples. In addition, the LTV method is a viable method in investigating and predicting the DNAPL migration in groundwater which can help the researchers in desinging the remediation tools.